Experimental measurement and statistical analysis of the RMS delay spread in time-varying ultra-wideband communication channel - Zahedi, Y. (Elsevier B.V., 2016)
The statistical analysis of the RMS delay spread is achieved based on the results obtained from an outdoor time-varying ultra-wideband (UWB) channel measurement. The paper reports on the RMS delay spread values, the cumulative distribution functions (CDFs) and the probability density functions (PDFs) for the measured channel configurations with their estimated parameters. Findings show how the RMS delay spread values are fluctuating for different channel configurations within the same measurement campaign. For example, 35 ns and 2.5 ns have been obtained for different channels. The differences in the measured instantaneous RMS delay spread leads to obtaining different PDFs that fit the measured data where Generalized Pareto distribution is dominant. The relation between the RMS delay spread and the channel path loss has been studied. Positive correlation is seen for all measured channels with different amounts. The highest correlation value is 0.7675 while the lowest is 0.2951. The coherence bandwidth analysis is also conducted, and the values are fluctuating as the case of the RMS delay spread. The obtained values varies between 325.3 MHz and 5.7 MHz.